К изучению жужелиц (Coleoptera, Carabidae) песков Харьковского района Харьковской области - Мищенко, А.А. (Вестник зоологии, 1974)
A study of the soil fauna resulted in finding 102 species of Carabidae belonging to
25 genera: 71 species in pine forests, 65 in overflow meadows and 60 — in glades; the
hill slopes and sandy outcrops are less rich, they number 42 and 34 species, respectively.
Holarctic (5 species), transpalearctic (37), European-Siberian (10), western palearctic (25),
European (4) , steppe (13), Mediterranean-pontian (3) and Mediterranean (2) elements are
presented. 21 species are registered in the North-East of the Ukraine for the first time.